New frontiers in antimicrobial leadership: an interview with Joan Butterton. (November 2018) - Greenway, Alice; Butterton, Joan
The Editor of Future Microbiology speaks to Joan R Butterton, M.D., Associate Vice President and Section Head for Antibacterials and CMV for the Infectious Disease therapeutic area at Merck & Co. Joan joined Merck in 2005 in the Department of Clinical Pharmacology where she served as co-chair of the HIV and HCV Early Development Teams and as Clinical Pharmacology Infectious Disease Lead. In these roles, she supported numerous programs within the HCV, HIV, antibacterial and CMV portfolio. Prior to joining Merck, Butterton served on the Faculty of the Infectious Disease Division at the Massachusetts General Hospital, conducting basic bench research in bacterial pathogenesis. She received her B.S (biology) from Yale University, an M. Phil. (history and philosophy of science) from Cambridge University, an M.D. from Harvard Medical School, and a Diploma in Tropical Medicine and Hygiene from the University of London. She completed her residency in internal medicine and a clinical/research fellowship in Infectious Diseases at the Massachusetts General Hospital (MGH) in Boston.